Screen traffic : movies, multiplexes, and global culture - Acland, Charles R., 1963- (e-Duke books scholarly collection., 2003)
In Screen Traffic, Charles R. Acland examines how, since the mid-1980s, the U.S. commercial movie business has altered conceptions of moviegoing both within the industry and among audiences. He shows how studios, in their increasing reliance on revenues from international audiences and from the ancillary markets of television, videotape, DVD, and pay-per-view, have cultivated an understanding of their commodities as mutating global products. Consequently, the cultural practice of moviegoing has changed significantly, as has the place of the cinema in relation to other sites of leisure. Acland explores this transformation by investigating the generation and dissemination of a new understanding of Hollywood movies. Through an innovative integration of film and cultural theory, and with close examination of promotional materials, entertainment news, trade publications, and economic reports, Acland presents an array of evidence for the new understanding of movies and moviegoing that has developed within popular culture and the entertainment industry.